Analysis of Science Education Students' Self-Efficacy in Developing Learning Products Through the Project-Based Learning Model - Gunawan, Gunawan; Herayanti, Lovy; Tamami, Fuad (Department of Physics Education, Universitas Mataram, 2025)
Developing innovative learning products demands high self-efficacy from prospective educators. The Project-Based Learning (PjBL) model offers the potential to develop this competency, yet its impact on the self-efficacy of postgraduate students requires in-depth analysis. This study aims to analyze the self-efficacy levels of Master's students in Science Education in developing learning products (presentations, videos, and a book chapter) implemented through the PjBL model. This study employed a descriptive method with a mixed-methods approach. Data were collected from 11 students through a Likert-scale self-efficacy questionnaire and open-ended responses, then analyzed using descriptive statistics and thematic analysis. The results show that students' overall self-efficacy is high (mean score > 4.18), with slightly higher confidence in asynchronous tasks such as video production (4.24) and writing a book chapter (4.25). The main finding identifies a gap between the very high motivation and growth mindset and the lower self-efficacy in higher-order thinking skills, particularly in data analysis and applying theory to practice (lowest score 3.82). It is concluded that PjBL is effective in building self-efficacy and motivation, while also successfully identifying crucial areas for professional development. Therefore, it is recommended that future PjBL implementation be enriched with more focused guidance on strengthening analytical and synthesis skills to optimize the competencies of future science educators.